Unveiling Heterospecific Pollen Deposition in Ranunculus Plants Along a Land‐Use Gradient Through DNA Metabarcoding - Susanne Werle; Anna Preußner; Kenneth Kuba; Sara Diana Leonhardt; Alexander Keller (Ecology and Evolution, 2025)
ABSTRACT Animal pollination, the transfer of pollen by animal agents, is essential for plant reproduction. Methods like microscopy and DNA metabarcoding have been used to investigate pollen transport and plant–pollinator interactions. DNA metabarcoding, in particular, is a reliable method to identify the origins of mixed pollen samples. Although it has mainly been used to study pollinators' dietary patterns, it does not provide insights from the plant's perspective, such as the type of viable pollen received. We aimed to explore the potential of DNA metabarcoding to analyse heterospecific pollen transfer to plants in semi‐natural and agricultural landscapes along a land‐use intensity gradient. We collected stigmas of three closely related Ranunculus species (R. acris, R. bulbosus and R. repens) from 20 grassland plots in Germany with varying land‐use intensities and flowering plant diversity and subjected them to internal transcribed spacer 2 (ITS2) metabarcoding. Our results revealed a nonlinear relationship between flowering plant species richness and heterospecific pollen richness on Ranunculus stigmas. The lowest heterospecific pollen diversity occurred in landscapes with intermediate plant species richness, whereas plots with low or high richness showed greater heterospecific pollen diversity. Reduced plant species richness, found mostly on intermediate and high LUI plots, forces pollinators to visit multiple plant species and thus increases heterospecific pollen transfer. Plots with intermediate plant species richness, on the contrary, likely provide a balanced mix of resources for pollinators, visiting multiple plant species within a foraging round and thus decreasing the amount of heterospecific pollen. Increased heterospecific pollen at high‐richness plots may result from competition in pollinator‐rich communities. Our results show that DNA metabarcoding is a powerful tool for assessing heterospecific pollen diversity, revealing that pollen transfer is heavily influenced by plant community composition. This approach provides novel insights into pollinator fidelity and potential pollination outcomes across diverse environments.